Use and effectiveness of rituximab in children and young people with juvenile idiopathic arthritis in a cohort study in the United Kingdom. (24th October 2018) - Kearsley-Fleet, Lianne; Sampath, Sunil; McCann, Liza J; Baildam, Eileen; Beresford, Michael W; Davies, Rebecca; De Cock, Diederik; Foster, Helen E; Southwood, Taunton R; Thomson, Wendy; Hyrich, Kimme L
Abstract: Objectives: Rituximab (RTX) may be a treatment option for children and young people with JIA, although it is not licensed for this indication. The aim of this study was to describe RTX use and outcomes among children with JIA. Methods: This analysis included all JIA patients within the UK Biologics for Children with Rheumatic Diseases study starting RTX. Disease activity was assessed at RTX start and at follow-up. The total number of courses each patient received was assessed. Serious infections and infusion reactions occurring following RTX were reported. Results: Forty-one JIA patients starting RTX were included, the majority with polyarthritis: polyarthritis RF negative [ n = 14 (35%)], polyarthritis RF positive [ n = 13 (33%)] and extended oligoarthritis [ n = 9 (23%)]. Most were female (80%) with a median age of 15 years [interquartile range (IQR) 12–16] and a median disease duration of 9 years (IQR 5–11). The median improvement in the clinical Juvenile Arthritis Disease Activity Score (cJADAS; three-variable 71-joint JADAS) from RTX start was 9 units ( n = 7; IQR −14–2). More than half reported more than one course of RTX. The median time between each course was 219 days (IQR 198–315). During follow-up, 17 (41%) patients reported switching to another biologic, including tocilizumab ( n = 8), abatacept ( n = 6) and TNF inhibitor ( n = 3). Three patients (7%) reported a serious infection on RTX (rate of first serious infection 6.2/100 person-years). Four patients (10%) reported an infusion reaction. Conclusions: This real-world cohort of children with JIA, the majority with polyarticular or extended oligoarticular JIA, showed RTX may be an effective treatment option for children who do not respond to TNF inhibitor, with a low rate of serious infections on treatment.